Irisin; a myokine with therapeutic and diagnostic potential in clinical dentistry - Saleem, Alina; Sarah Ghafoor (Journal of the Pakistan Medical Association, 2023)
Irisin is a novel adipomyokine which has extensive systemic and local effects in different tissues of the body. The scientific interest in understanding the physiological roles of irisin in the body has increased tremendously in the past few years due to its vast therapeutic potential in different fields of medicine. The current narrative review was planned to describe the molecular mechanisms by which irisin regulates oral hard and soft tissues. The information gleaned provided useful insights for future researchers to investigate newly discovered roles of irisin in craniofacial health and disease, and to explore the potential of irisin as a promising therapeutic and diagnostic agent in clinical dentistry. Key Words: FNDC5, Irisin, Human periodontal ligament cell, Human dental pulp stem cell, Bone, Regeneration.